ITKs RELATED TO PISCICIDAL AND FISH ATTRACTANTS FROM NAGAON DISTRICT OF ASSAM - SAHA, BISWARUP; DEVI, RAJITA; PANDIT, ARUN; KASHYAP, DIPANJAN (Journal of the Inland Fisheries Society of India, 2021)
Predatory fishes, minnows, and aquatic insects are common in fishponds in India. Predatory fishes may enter aquaculture farms through watersupplies or along with seed brought into the fish farm and can eat and/or compete with cultured carps (Jhingran, 1983).There are large number ofplants belonging to different families, whose products are being used for controlling unwanted fish population not only in India but also other partsof the world. These plants produce poison to protect themselves from external invasion (Weiss, 1973). Plant poisons are extracted from flowers,bark, pulp, seed, fruit, root, leaves and the entire plant (Lamba, 1970; Tyler, 1986). More than 60,000 plant species are used for various purposes all over the world (FAO, 19914). Approximately 1190 pure chemical substances extracted from higher plants are used in medicine throughout the world (Farnsworth et al., 1985). It has been reported that there are 112 plants having piscicidal action. Out of these, more than 40 plants grow in Northeast India (Ramanujam and Ratha, 1980). Plant extracts are referred to as botanicals and when poisonous to fish are called piscicides (Burkill, 1985). Such piscicidal plants containÂ different active ingredients known as alkaloids such as nicotine, pyrethrum, ryania, rotenone, coumerin, resin, akuammine, tannins, saponins and diosgenin (Wang and Huffman, 1991). However, these alkaloids are toxic to fish and other aquatic organisms at high concentrations and wear off within a short time (Crandall and Goodnight, 1962; Olaifa et al, 1987; Kulakkattolickal, 1987 and Adewumi, 1990)